WORK WITH THE WEB-TABLES USING THE LIST OF HYPERLINKS - Vladimir Nikolaevich Belov (Современная наука и инновации)
We have a task, which, we came to the conclusion that it is necessary to create a software product that will take most of the work. Presented in this article, the utility is aimed at automating human activities. To create a program was used the development environment Visual Studio Express C#. In particular, this utility is aimed at creating a web-tables with a large amount of data. The program is written in C# programming language. The code of a program freely described how it works and the reasons for the creation. All methods and algorithms that uses the utility described in the article. At the moment the program is fully completed and ready to use. Utility was experimentally tested and the results verify the conclusions that the process of working with WEB tables has accelerated several times.